DETERMINANTS OF HOUSEHOLD FOOD SECURITY AND COPING STRATEGY: (EVIDENCE FROM AMARO WOREDA OF SOUTHERN ETHIOPIA) - Diramo, Alemnesh; Negash, Rahmeto; Abebe, Agidew (International Journal of Research -GRANTHAALAYAH, 2018)
The study was conducted in Amaro Woreda of southern Ethiopia with the main objectives to identify the main determinants of household food Security. Data were analyzed by simple descriptive statistics (percentage, frequency and mean), inferential statistics (Chi-square and t-test) and logistic regression (binary logit) model. Household calorie acquisition was used to measure the status of household food security. Through systematic sampling method 151 respondents were identified. Among those 40.4% of the respondents were food insecure and 59.6% were food secure. The logistic model was initially fitted with 11 variables of which five were found to be significance effect on the household food security. Cultivated land size, livestock holding, education level, household labor and annual gross household income were significantly affecting household food security. Farm households have employed different coping strategies including sale of livestock, reduce size of meals and reduce number of meals at initial stage of food shortage and receive food aid, sale/consume seed meant and reduce size of meals at sever stage of food shortage. Improved food security is attained along with the increase in the size of cultivated land and livestock holdings. Improved technologies that increase the productivity of land and livestock should be given prior attention.